2020
DOI: 10.1108/jaar-05-2020-0095
|View full text |Cite
|
Sign up to set email alerts
|

Too big to fail? Accounting for predictions of financial distress in English professional football clubs

Abstract: PurposeThis paper analyses English Premier League (EPL) and English Football League (EFL) championship clubs during the period 2002–2019 to anticipate financial distress with specific reference to footballs' Financial Fair Play (FFP) regulations.Design/methodology/approachData was collected for 43 professional football clubs competing in the EPL and Championship for the financial year ends 2002–2019. Analysis was conducted using the Z-score methodology and additional statistical tests were conducted to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 52 publications
3
35
0
3
Order By: Relevance
“…In English football, Plumley, Serbera and Wilson (2020) did state that some EPL clubs were performing poorly against bankruptcy measures with a notable excpetion being the 'big 6' clubs in the league. Our findings do not show evidence to support a financial problem in the EPL based on our aggregate data.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In English football, Plumley, Serbera and Wilson (2020) did state that some EPL clubs were performing poorly against bankruptcy measures with a notable excpetion being the 'big 6' clubs in the league. Our findings do not show evidence to support a financial problem in the EPL based on our aggregate data.…”
Section: Discussion and Contributionsmentioning
confidence: 99%
“…a situation where, by due legal process, control of an organisation has passed from its directors to an outside independent party acting in the interests of the creditors) in the first four top divisions have occurred. More recently, Plumley, Serbera and Wilson (2020) found that the majority of clubs in the EPL and English Football Championship (tier 2 of English football) were in significant financial distress when measured against bankruptcy indicators and that in some cases this situation had worsend post-FFP. In France, Scelles et al (2018) had identified 79 cases of insolvency between 1970 and 2014 in the top French divisions but only seven within the first tier.…”
Section: Soft Budget Constraint Approach As An Explanation Of the Financial Crisis In European Football?mentioning
confidence: 99%
“…If a company determines that its current debt payment obligations exceed its current cash flow, it may choose the option to consider bankruptcy claims to reduce its debt obligations. Financial distress in business is not a new phenomenon, but it has become an issue of special attention during the last decade since the global recession of 2018 [61]. Many unexpected situations, such as the COVID-19 pandemic, have led to the declaration of bankruptcy by many companies [62].…”
Section: Predicting Bankruptcy Using Altman's Z-score Model and Determining The Possibility Of Fraudulent Financial Reporting Using The Bmentioning
confidence: 99%
“…Additionally, it was found that the big clubs, those insolvent and those located in the Southeast region have a higher debt. The sports literature points out that in soccer clubs, those considered large tend to have higher indebtedness, although the risk of insolvency is greater for small clubs (Baroncelli & Lago, 2006;Dantas et al, 2015;Ferri et al, 2017;Hagen & Cunha, 2019;Plumley et al, 2021). Table 6 presents the results of the Two-sample Wilcoxon rank-sum (Mann-Whitney) test to verify if there are significant differences in the debts of clubs with these characteristics.…”
Section: Indebtedness Profile Of Football Clubs In Brazilmentioning
confidence: 99%
“…Second, the establishment of a salary cap, which in Brazil could be related to the division, as it tends to help clubs maintain costs. Finally, those responsible for organizing football should review the financial regulations to provide greater consistency to help clubs achieve long-term financial sustainability (Plumley et al, 2021).…”
Section: Financingmentioning
confidence: 99%